MODAL ANALISIS PADA ROTARY KILN DENGAN MENGGUNAKAN METODE ELEMEN HINGGA - Wahyu Rahmat Hidayat; Dedi Suryadi (UNIB Press, 2022)
This research is based on the general damage to the rotary kiln due to continuous use. Then the results from the burned in a Rotary Kiln So we need a prevention to overcome it. Testing the vibration mode on a rotary kiln machine is a solution to overcome the limit on the use of the finite element menthod. With the completion procedure of finite element software with the step of Rotary Kiln Geometry Modeling Process, Rotary Kiln Geometry Import Process, Rotary Kiln Geometry Import Process, Material Data Input Process, Meshing Process, Determination of Boundary Conditions, Running Process, and Port Processing. The results of this study are from the finite element simulation obtained in the form of the frequency value of the natural response of the structure and the deflection due to vibrations that occur in the rotary kiln Indarung IV PT Semen Padang. And it was concluded that the vibration mode experienced by the rotary kiln has a natural frequency value, the vibration mode of the rotary kiln structure obtained a maximum value of 63.3 Hz, while the minimum value obtained a value of 41.805 Hz. The maximum deflection of the rotary kiln is obtained from the analysis results of 0.058981 mm while the minimum deflection value is 0.045 mm.